Parameter of "fundamentals" determination of criminal penalties for women by Islamic criminal law in hudud cases - Muhammad Husni, Ahmad; Mohammad, Abdul Basir; Mohd Nor, Amir Husin; Laluddin, Hayatullah; Samuri, Mohd. Al Adib; Che Omar, Nurhayati (American-Eurasian Network for Scientific Information (AENSI Publisher), 2012)
Every offense committed by aman would receive appropriate punishment throughthe determination ofIslamic law ornationallegislation. Thissentenceincludes wholehuman beings regardless ofgender. Therefore, there are noprivilegesgranted to themale offenders thanfemale offenders, and vice versa.Despite the clear position between the subjects in terms of ability and responsibility to bear criminal sanctions, but the fact is that the execution of offenders difference between men and women sometimes giving rise to the question of why the availability of the gap between them when all men are equal for God Almighty nor the laws of human invention?Thus the researchers tried to clarify this question and explain in detail the types of punishment and the implementation to both male and female offenders by bringing the basics felt to be a parameter in establishment and execution of the sentence against them. To produce a conclusion that can answer the problems that arise, the methodology used in this research is to use the method of documentation, textual analysis and interviews. Documentation method carried out by examining the documents related to this matter. This method used in collecting and observing all written or pictorial material with the status of documentation such as books, theses, magazines, journals, etc. Subsequently, make modification and compare between all the materials to reach the conclusion. Thus, results from this study, researchers found that the difference between the offender executions of men and women were present in both Islamic law and civil with each having its own grounds